Pengembangan Media Pembelajaran Pop-up Book Berbasis Kontekstual Muatan Pelajaran PPKN Kelas IV Sekolah Dasar - Izzah Salsabila; Mimin Ninawati (Universitas Pendidikan Mandalika, 2022)
This study aims to develop a product which is a Pop-up Book media in the content of civic education about religious diversity material in Indonesia for 4th-grade students. This study used the R&D method (Research and Development) with a 4D model. The stages in the 4D model consist of Define, Design, Develop, and Disseminate. This research was conducted at SDN Slipi 01 Pagi involving 29 students from class IV B. The data were collected using questionnaires distributed to media experts, material experts, and students. The data analysis technique used descriptive statistical analysis as percentage analysis. The results of the research showed that the Pop-up Book media development had an average percentage of 92% in the